SSCP analysis of paraffin wax embedded tissues in a family with an atypical form of Fabry disease. Issue 5 (October 1996) - Madsen, Kirsten Marie; Hasholt, Lis; Berger, Johannes; Sørensen, Sven Asger
Abstract : To investigate the distribution of a single base pair mutation within a family with one known case of Fabry disease, DNA from paraffin wax embedded necropsy material was studied using single-strand conformation polymorphism (SSCP) analysis. The proband, who presented with an atypical form of Fabry disease, had a G to A transition in exon 6 of the α-galactosidase A gene. This patient had mainly cardiac symptoms and late onset disease. Further cases of coronary disorders occurred in this family, including the proband's brother who died at 42 years of age of a cardiac disorder. Formalin fixed, paraffin wax embedded material from the brother and two more distant relatives was available for analysis. SSCP analysis showed that the proband's brother also carried the G to A transition. Thus, the atypical form of Fabry disease and unrelated cardiac diseases with similar clinical symptoms occurred within a single family. The variant form is rare but may account for a few of the numerous cases of cardiac disease in men and should be considered when clusters of cases of cardiac disease occur within a single family.